Quick-assembly units in steel frames of multi-storey buildings - A. R. Tusnin; I. V. Myl’nikov (Vestnik MGSU)
Introduction. In the conditions of steel construction development, it is relevant to create a nomenclature of standard unified products, assemblies and parts of steel frames, which will allow engineers to create projects of modern prefabricated buildings with less labour costs, and builders to implement them quickly and efficiently. The joints of the column junction in height and their coupling with the floor beams are considered. In these design solutions, the forces are transmitted by direct contact of the end surfaces of the connected elements, which avoids the execution of mounting welds and a large number of bolted connections. As a result, when using contact connections, the installation time and the cost of construction of the metal frame are reduced.Materials and methods. When considering contact problems, the Saint-Venant principle is not applicable, it is important to explore the immediate areas of the contact surfaces of the elements. The nodes were developed using the example of a typical frame of a five-storey building with cell sizes from 3 × 3 to 6 × 6 m with structural elements of specified sections.Results. The possible contact connections of the frame elements are presented, which allow assembly only by installing them on top of each other and finishing adjustment. Such connections, due to the work of the contact surfaces on the crumple, allow transmitting not only longitudinal forces, but also some of the bending moments.Conclusions. The proposed options for column joints and beam-to-column junctions are non-typical and not previously used in engineering practice. For the widespread use of such units in the practice of designing steel frames of multi-storey buildings, it is necessary to investigate their bearing capacity and deformability comprehensively. It is of interest to study the influence of the geometric parameters of the connecting elements on the stiffness of the nodes and on the stress-strain state of the frame as a whole. The present research will be conducted using computer software and experiment.